2016
DOI: 10.1371/journal.pone.0150185
|View full text |Cite
|
Sign up to set email alerts
|

Ultradeformable Archaeosomes for Needle Free Nanovaccination with Leishmania braziliensis Antigens

Abstract: Total antigens from Leishmania braziliensis promastigotes, solubilized with sodium cholate (dsLp), were formulated within ultradeformable nanovesicles (dsLp-ultradeformable archaeosomes, (dsLp-UDA), and dsLp-ultradeformable liposomes (dsLp-UDL)) and topically administered to Balb/c mice. Ultradeformable nanovesicles can penetrate the intact stratum corneum up to the viable epidermis, with no aid of classical permeation enhancers that can damage the barrier function of the skin. Briefly, 100 nm unilamellar dsLp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 78 publications
1
13
0
1
Order By: Relevance
“…It should be emphasized that canyons have been so far only described in a few scientific manuscripts. They were indicated as an important, alternative pathway of diffusion of substances into the skin, including a transport route for dermal formulations in the form of nanoparticles [ 26 , 27 , 28 , 29 , 30 ]. Some studies have shown that canyons are characterized by limited resistance to penetration of xenobiotics applied to the skin [ 1 , 26 , 27 , 28 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that canyons have been so far only described in a few scientific manuscripts. They were indicated as an important, alternative pathway of diffusion of substances into the skin, including a transport route for dermal formulations in the form of nanoparticles [ 26 , 27 , 28 , 29 , 30 ]. Some studies have shown that canyons are characterized by limited resistance to penetration of xenobiotics applied to the skin [ 1 , 26 , 27 , 28 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“… 16 Furthermore, the addition of a detergent, sodium cholate, to TPL archaeosomes has been shown to generate ultradeformable archaeosomes (UDA) for topical delivery of vaccines to the skin. 19, 20 Nevertheless, despite these successes, the TPL archaeosome formulations typically used are relatively complex and comprise multiple lipid species. In attempts to overcome this, we have previously tested various semi-synthetic phospho-glyco-archaeol archaeosomes which offer some advantages over traditional TPL formulations while retaining adjuvanticity.…”
Section: Discussionmentioning
confidence: 99%
“…The polar lipids in archaeosomes are responsible for the pronounced capture by phagocytic/immature APCs, resulting in strong CD4 + and CD8 + CTL responses to the entrapped antigens . The ultra‐deformable archaeosomes can penetrate the intact SC and reach the viable epidermis in the absence of classical permeation enhancers . Although no report is yet available on a genetic vaccine topically delivered by archaeosomes, the ultradeformable archaeosomes could be a promising platform.…”
Section: Advanced Technologies For Transcutaneous Gene Deliverymentioning
confidence: 99%
“…86 The ultra-deformable archaeosomes can penetrate the intact SC and reach the viable epidermis in the absence of classical permeation enhancers. 87,88 Although no report is yet available on a genetic vaccine topically delivered by archaeosomes, the ultradeformable archaeosomes could be a promising platform.…”
Section: Lipid Vesiclesmentioning
confidence: 99%